2004
DOI: 10.1002/jmri.20000
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of T2 relaxation changes in articular cartilage with in situ mechanical loading of the knee

Abstract: Purpose: To devise a method for producing in vivo MRI images of the knee under physiologically significant loading, and to compare and evaluate the changes in cartilage characteristics before and during in situ compression of the knee. Material and Methods:A total of 26 asymptomatic subjects were imaged on a 1.5 Tesla Philips Intera scanner using a commercially available knee coil. Routine anatomical images were followed by T 2 map acquisition. These scans were repeated following in situ compression of the kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 17 publications
4
65
0
Order By: Relevance
“…Consistent with previous studies, we observed between 2%–15% reductions in T 1ρ and T 2 times across the tibial compartments with loading. [910] The largest changes were observed in T 1ρ relaxation times of the MT in subjects with OA (15%) and healthy controls (12%). Previous literature has linked T 1ρ times to both glycosaminoglycan content and tissue hydration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous studies, we observed between 2%–15% reductions in T 1ρ and T 2 times across the tibial compartments with loading. [910] The largest changes were observed in T 1ρ relaxation times of the MT in subjects with OA (15%) and healthy controls (12%). Previous literature has linked T 1ρ times to both glycosaminoglycan content and tissue hydration.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to literature that reported significant reductions in the femoral cartilage T 2 times in response to loading, and no differences in the tibial cartilage. [10] However, these authors used coronal slice acquisition and evaluated subregions divided into six medial-to-lateral subcompartments. Ultimately, the regions reported cannot be directly compared to those evaluated in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies which evaluated the effect of exercise (22) or alternative loading of joint cartilage (48,49) using scan-rescan protocols found differences of T 2 on the order of 0.6 ms to 9.6 ms. Two of these studies used the linear fitting method for calculating T 2 (22,48) while the method used by the third study was unspecified (49). It is uncertain if a non-linear solution for T 2 may alter the findings of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nishii et al [54] compared T2 values and distribution in normal volunteers and patients with hip dysplasia; graded plain radiographs into normal, prearthritic, and mildly arthritic hips; and found no difference in T2 relaxation times among the different radiographic grades. T2 mapping is also sensitive to the loading state of the joint, which may alter T2 signal independent of cartilage damage if joint unloading before scanning is not controlled [2,40,49,52]. Finally, T2 values are sensitive to the orientation of the collagen fibers relative to the B0 magnetic field due to the magic angle effect.…”
Section: àmentioning
confidence: 99%